PENGARUH MEDIA IKLAN, CITRA MEREK DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK PERUMAHAN - Okta Karneli, Ibnu Suharwanto, Seno Andri, (Jurnal Ilmu Administrasi Negara, 2020)
Effects of Advertising Media, Brand Image and Product Quality on Housing Product Purchase Decisions Study at PT. Asta Karya (Housing Astam House Pekanbaru). This study aims to determine the effect of advertising media, brand image and product quality on purchasing decisions of study housing products at PT. Asta Karya (Housing Astam House Pekanbaru). The study was conducted with partial least square (PLS) analysis with 83 respondents. Based on the results of the analysis it was concluded that advertising media had a significant effect on purchasing decisions. This means that the better the advertising media, the purchasing decision will increase. Furthermore, brand image has a significant effect on purchasing decisions. This means that the better the brand image, the purchasing decision will increase. Furthermore, product quality has a significant effect on purchasing decisions. This shows that while the quality of the product is good, the purchasing decision will be higher. The R Square value of 0.6505 shows that 65.05% changes in the value of purchasing decisions are influenced by advertising media, brand image and product quality.